The inclusive education: commitment of a society - Vera Pagaza, Miryam (2018)
If we mention the inclusive education, it is necessary to remark a topic of interest in the work of quality to the children with SNE: teachers’ attitude. Attitude defined as the stance adopted when one deal with this new challenge full of mixedfeelings in favour or against, emotions, beliefs, perceptions, but mainly a projected vision to the achievement of the expected learnings. This paper approach the dimensions that help to develop an effective inclusion from regular classroom. The elements that influence in the teacher’s attitude could limit their labor or contribute to improving their practices; namely: teaching experience, initial and continuous training, typical characteristics of students with SNE, support resources.There is an urgent need to generate a culture open to the diversity in the context of an educational policy that assure the equity and quality to respond the heterogeneity.